Assessment of transportation network vehicle services from their drivers' perspective - Mirandilla, Clinton S.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The study aimed to assess Transportation Network Vehicle Services (TNVS) by gathering data from the drivers and operators. The productivity, impact in traffic congestion, amount of supply, profitability, and general problems and concerns of TNVS in Metro Manila were determined in the study. Data regarding TNVS are very limited especially that the biggest players in the platform, Uber and Grab, are closed to providing substantial information regarding their system. Yet, the system is still in need of analysis for the country to be able to adapt to the new technology most especially in regulating these services. All data were gathered through online surveys directed to drivers and operators. Descriptive statistics was used to present and organize the data. Statistics from the sample were projected to parameters of the population using Z-tests and Student's T-test. Productivity and impact in traffic of the TNVS system was assessed by comparing it to the productivity and impact of other public transportation modes through passenger-kilometers (PKM) and PCU-kilometers. The amount of supply was analyzed by plotting the drivers' working hours schedule into a per hour count of online TNVS units daily. The profitability of drivers in TNVS was determined by breakeven analysis. The study found out that when the fleet size is 91,000 to 97,000, TNVS provide at least 36,000 units from 8AM to 9PM during weekdays and generate 374,034 to 592,375 trips per day in Metro Manila. However, when TNVS compete with other public modes of transportation, there is inefficiency since TNVS have greater impact in traffic compared to other public modes of transportation in total while delivering inferior productivity. The study also concluded that being a part-time driver operator is more profitable than being a full-time driver-operator. The risks of loss and very low income are very high for full-time driver-operators of TNVS.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Taxicab drivers; Ridesharing; Transportation network vehicle services (TNVS).